Die Puppen der mitteleuropäischen Zünsler : Charakteristik, Bestimmungstabelle der Unterfamilien, Unterfamilien Galleriinae, Pyralinae und Phycitinae (Lepidoptera: Pyraloidea, Pyralidae). - Patočka, Jan (Contributions to Entomology = Beiträge zur Entomologie, 2001)
The pupae of Central European Pyralidae (Lepidoptera) are characterized and a key for the identification of their 9 subfamilies is added. The subfamilies Galleriinae, Pyralinae and Phycitinae (49 genera, 75 species) in the pupal stage are characterized, described and figured, the identification keys for their genera and species and some data of their bionomics and habitats are added. The present system of this groups is discussed on the basis of pupal characters.